Psychometric validation of the Reported and Intended Behaviour Scale (RIBS) in Hungary with a particular focus on 'Don't know' responses and further scoring recommendations - D. Őri; E. Vass; K. Vajsz; K. Vincze; V. Sztancsik; A. Szemán-Nagy; L. Simon (BMC, 2023)
Abstract Aims Reported and Intended Behaviour Scale (RIBS) was designed to measure mental health stigma-related behaviors in the general public. We aimed to examine its psychometric properties and validate the scale in a Hungarian non-clinical community sample. The secondary aim of this study was to assess the appropriateness of the current scoring recommendations of 'Don't know' responses being coded as neutral, which had never been investigated before. In addition, we provide an overview of the results of already existing studies on the scale. Methods Hungarian participants completed the RIBS within this cross-sectional online survey study and were considered non-clinical individuals based on a cut-off point of the Global Severity Index T score of 63 on the Symptom Checklist-90-Revised. Confirmatory factor analysis, reliability measures, and comparative analyses were performed. Results Of the n = 5,701, n = 5,141 participants were included in the analysis. The mean age was 27.8 ± 11.1 years, and 89.2% (n = 4,587) of the sample were female. The unidimensional structure was supported by good model fit indices (RMSEA = 0.031, CFI = 0.999, TLI = 0.996, and WRMR = 0.006). Internal consistency of the RIBS and its test-retest reliability with a 5-month follow-up period were found to be good (Cronbach's alpha = 0.88 and ICC = 0.838). We found statistically significant differences between the total scores when the 'Don't know' responders were excluded from the sample or when they were coded as neutral as recommended by the scale authors (16 (IQR:13-18) vs. 15 (IQR:13-18) p < 0.0001). There were also statistically significant differences between 'Neither agree nor disagree' and 'Don't know' participants in several aspects of lived experiences of mental health problems. Conclusions The RIBS demonstrated good psychometric properties and can be transferred to the Hungarian context. It will be a valuable tool in assessing stigmatizing behavior and testing the efficacy of antistigma programs. Our results suggest that 'Neither agree nor disagree' and 'Don't know' responses bear different meanings, and coding should account for this.